IPhone and iOS forensics : investigation, analysis, and mobile security for Apple iPhone, iPad, and iOS devices - Hoog, Andrew (Syngress, 2011)
As sales and usage of iPhones increase so does the demand on organizations that conduct examinations on this device. iPhone and iOS Forensics takes an in-depth look at methods and processes that analyze the iPhone/iPod in an official legal manner. All of the methods and procedures outlined in the book can be taken into any court room. This book details the iPhone with information data sets that are new and evolving, with official hardware knowledge from Apple itself to help aid investigators. iPhone market share has increased to 50% of worldwide mobile phone usage Employment in digital forensics is projected to grow by 30% over the next 5 years with the US Federal Government looking for 10K qualified pros in 2009 alone.